Person-centred care for dementia patients (front-end Android app) - Cheung, Zhi Heng (Nanyang Technological University, 2024)
In Singapore, the rising number of individuals with dementia has created significant challenges for caregivers. To address this issue, the Person-cEntered cARe software system (PEAR) was developed to support healthcare providers in delivering personalised care to dementia patients in a daycare centre. The PEAR system facilitates person-centered care by providing timely and relevant information, ensuring efficient and effective care delivery. The platform is available in both web and mobile versions; the mobile application enables caregivers to access critical information on the go, while the web application offers additional functionalities for managing complex tasks. This project focused on improving the mobile app's functionality, fixing bugs and accelerating development. The author played a key role in upgrading the Expo SDK, developing new features, and conducting manual, user acceptance and automated testing. By improving the user experience and overseeing project management, the author contributed to delivering a more efficient, stable and user-friendly application. The author’s contributions have paved the way for future improvements, including further development of automated testing and the implementation of responsive design. Additionally, the author has provided comprehensive documentation to assist future developers in their ongoing work. This effort ensures that future developers can build upon the existing codebase with greater ease and flexibility, enhancing the project’s sustainability and success.